Implementasi Container Live Migration Antar-Cloud Provider Menggunakan Podman dan CRIU - Muhammad Abdul Aziz; Adhitya Bhawiyuga; Fariz Andri Bakhtiar (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2020)
Cloud computing is an important technology and is quite widely used today. Some companies that provide cloud computing services now are Google, Microsoft, IBM and Amazon. One of the popular cloud computing services is virtualization. Virtualization allows a single machine to perform multiple roles of a running service. In the application of virtualization in cloud computing, live migration is a very important process. Live migration of a virtual machine requires the entire state of the source virtual machine to be moved to the destination virtual machine. On the other hand, there is a live migration technique called container live migration which only requires the state of the service to be moved. This research applies container live migration techniques to move services from one virtual machine to another, without having to move the entire state from the source virtual machine to the destination virtual machine, using Podman and CRIU. With Podman, a service can run as an isolated process, independent of its surroundings. With CRIU, services can be stopped and transferred from one machine to another. The results of functional testing show that the proposed live migration method is capable of moving services between different cloud providers. The results of testing the implementation of container live migration between cloud providers using Podman and CRIU show an average downtime of 34.618 seconds, and an average migration time of 71.627 seconds.